A Retrospective Study of Chemotherapy‐Related Extravasation Events in Dogs and Cats - Elise Martens; Rachel Hritz; Craig Clifford; Christine Mullin; Corrine Camero; Kai‐Biu Shiu; Catherine Chan; Chelsea delAlcazar; Carol DeRegis; Lindsay Donnelly; Bryan Marker; Katarzyna Purzycka; et al. (Journal of Veterinary Internal Medicine)
ABSTRACT Background Chemotherapy extravasation is a potentially serious complication. There is a paucity of information in the veterinary literature investigating extravasation events, treatments, and outcomes. Objective Evaluate chemotherapy extravasation events and treatments in dogs and cats, adverse events (AEs), and overall outcomes. Animals Twenty dogs and three cats were included. Methods Retrospective, multicenter, descriptive study including dogs or cats with suspected extravasation from chemotherapy. Information obtained included: signalment, extravasation details and treatment provided, AEs graded according to VCOG‐CTCAE v2 criteria, and outcome. Results The most common drug extravasated was doxorubicin, followed by carboplatin. Carboplatin extravasation (n = 5) resulted in Grades III–IV AEs, all of which required surgical debridement. Doxorubicin extravasation (n = 9) resulted in Grades 0–V AEs, two of which amputation was ultimately recommended, and one of those two was euthanized instead. Extravasation of vinca alkaloids (n = 5) and rabacfosadine (n = 1) resulted in Grades II–III AEs, all managed in the outpatient setting. Mitoxantrone (n = 2) and dacarbazine (n = 1) extravasation resulted in no clinical signs associated with extravasation injury. Seventy‐eight percent (18/23) cases had extravasation occur during one of the first four treatments of chemotherapy, with 30% (7/23) occurring during the first chemotherapy treatment. Conclusions and Clinical Importance Most cases (20/23) had mild to moderate or no AEs. Findings support that carboplatin should be considered a vesicant.